Comparison of Intermittent vs. Continuous Phototherapy in the treatment of Non-Haemolytic Neonatal Hyperbilirubinemia - Irfan Ullah, Irfan Khan, Khalil Ahmad, Khalid Khan, Muhammad Shafiq, Saeed Ullah, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Phototherapy is used in the treatment of hyperbilirubinemia in initial life-span of neonates. Our objective was the comparison of continuous vs intermittent phototherapy in the reduction of total serum bilirubin, bilirubin decrease rate, phototherapy time and hospital stay in non-haemolytic hyperbilirubinemia neonates. Place and Duration: The study was conducted at department of Pediatric medicine in Qazi Hussain Ahmad Medical Complex, Nowshera for the duration of six months from 16th January 2021 to 15th July 2021. Methods: The study involved 160 neonates with birth weight ≥2000 gm and age was above 34 weeks. They were randomly assigned to group A who were given continuous phototherapy for 3hrs and 50 mints and then rest for 45mints and group B who were given intermittent phototherapy for 3 hours and then rest for next 3 hours and so on. The levels of TSB were calculated in both groups and their comparison was made at every 12, 24 and 48 hrs after the start of phototherapy. Results: The mean of total serum bilirubin on admission was 16.01 ± 3.91 mg / dL for the continuous group and 15.21 ± 1.12 mg / dL for the intermittent group. The TSB mean after 12, 24 and 48 hrs. for continuous phototherapy was 13.30 ± 2.3 mg / dl, 11.1 ± 2.01 mg / dl, 9.26 ± 0.92 mg / dl and 13.1 ± 1.70 mg / dL, 9.54 ± 1.7 mg / dL, 8.9 ± 0.61 mg / dl (p <0.05) for the intermittent group, respectively. The mean rate of decrease in serum concentration of bilirubin was 0.30 ± 0.14 mg / dl / h in group A and 0.19 ± 0.07 mg / dl / h in group B (p = 0.5). There was no big variance between the mean hospital stay in groups A and B (p = 0.550). Conclusions: Intermittent phototherapy is a better choice than continuous phototherapy in the treatment of non-haemolytic hyperbilirubinemia, with added benefits such as less frequent disruption of the mother-child relationship and reduced radiation therapy.